Editorial: biomarkers in neurology - Mondello, Stefania; Salama, Mohamed Mosaad; Mohamed, Wael Mohamed Yousef; Kobeissy, Firas H. (Frontiers Media S.A., 2020)
Neurological disorders constitute a major health and socioeconomic problem. They represent the second cause of death and the leading cause of disability throughout the world. Despite the implementation of strategies and intervention programs to reduce the burden, over the past 25 years, the incidence, prevalence, mortality, and disability rates of neurological disorders are rising globally, mainly due to population aging and growth (1). This has placed heavy pressure on health-care systems pointing out the urgent need to identify new strategies to improve patient outcomes and reduce health costs by enabling more effective drug development and establishing a more personalized medicine approach.